What are the differences in patient-reported functional outcomes and recovery time between arthroscopic and open surgical repair for full-thickness rotator cuff tears in adults ? : A Systematic Review - Virta Andhika; Mohammad Erstda Trapsilantya (The International Journal of Medical Science and Health Research, 2025)
Introduction: Full-thickness rotator cuff tears are a major cause of shoulder pain and disability, commonly treated with either open or arthroscopic surgical repair. The optimal surgical approach remains debated, with extensive research comparing the two techniques. This systematic review aims to consolidate current evidence on the differences in patient-reported functional outcomes, recovery time, and complication rates between arthroscopic and open repair for full-thickness rotator cuff tears in adults. Methods: A systematic review was conducted following PRISMA guidelines. We searched PubMed, Springer, Semantic Scholar, Google Scholar, and Wiley Online Library for comparative studies published since 2015. The search used keywords based on the PICO framework, including "Rotator Cuff Tears," "Arthroscopic Repair," and "Open Surgical Repair." We included randomized controlled trials and cohort studies comparing arthroscopic and open techniques in adults with full-thickness tears that reported on functional outcomes. A total of 25 studies met the inclusion criteria. Results: The analysis of 25 studies, including 11 randomized controlled trials and six systematic reviews, consistently showed no significant long-term difference in functional outcomes between arthroscopic and open repair. Both methods resulted in comparable improvements as measured by scales like the Constant-Murley and ASES scores. Some evidence suggested that arthroscopic repair provides less pain and better function in the immediate postoperative period (e.g., within 72 hours to one month), but this advantage was not sustained. Re-tear and complication rates were also found to be similar between the two groups in most studies. Conclusion: Based on the synthesized evidence, both arthroscopic and open repair techniques are equally effective for treating full-thickness rotator cuff tears, yielding similar long-term functional outcomes. While arthroscopic surgery may offer a transient early recovery benefit, this does not translate into long-term superiority. The choice of surgical technique should be guided by surgeon expertise, patient preference, and resource considerations rather than an expectation of different clinical outcomes.